Pemanfaatan Teknologi Cloud Computing Dalam Reformasi Birokrasi Guna Mewujudkan Kejaksaan Yang Profesional, Komunikatif Dan Akuntabel - Sudirdja, Rudi Pradisetia (Jurnal Hukum & Pembangunan, 2020)
Cloud computing is so populer and it has become a hot word in the tech world, especially in the era of industrial revolution 4.0 which requires speed, accuracy and precision in the business process. Cloud computing is a combination of the use of computer technology (computing) and Internet-based development (cloud), resulting in a model of processing activities, storage, software and other services provided as an integrated virtual source on an internet network. This paper examines the use of cloud computing in the implementation of bureaucratic reforms, improving the quality of prosecutors professionalism, and providing communicative and accountable public prosecutors. The results show: (1). Cloud computing is able to accelerate the implementation of the business (process), so relevant is applied in assisting bureaucratic reform in the Attorney. (2). Utilizing cloud computing by making it a data bank or digital library will facilitate prosecutors in accessing Legal Resources as well as Technical Guidance of the Attorney, thus promoting professionalism. (3). Cloud computing can serve as a means of communication as a means of retaining public performance that is easily accessible to the public.